IMPLEMENTASI AIDA DALAM PERANCANGAN SCRIPT DIGITAL CAMPAIGN CREATIVE VIDEO INTERVIEW TSP SQUAD - Agnes Java Ayu Septianti; Santoso, Hudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to analyze the role of a script writer in designing creative video interviews for the TSP Squad digital campaign using the AIDA (Attention, Interest, Desire, Action) approach. A descriptive qualitative method was employed through in-depth interviews. The results show that AIDA-based script structuring creates an effective communication flow, from introducing informants to delivering experiences and values. Storytelling that highlights personal growth, a supportive environment, and social connections enhances audience interest and emotional engagement. Thus, the AIDA approach is considered effective in supporting message delivery and digital campaign objectives.